Expanded answers to bureaucratic questions: Negotiating access to public healthcare - Bonnin, Juan Eduardo (2014)
This article analyzes expanded responses to statistical-epidemiological questions at a mental health outpatient service at a public hospital in Buenos Aires, Argentina. Bureaucratic questioning is a highly routine activity which supplies information to the biopolitical apparatus of the modern State. We understand that expanded answers are meaningful actions which not only serve individual, local tactics (such as raising personal concerns), but also index higher contextual levels. In this sense, resisting the constraints of a question may also imply resisting State-defined policies of biopolitical classification and exclusion. We examine, from a discursive interactional point of view, 41 admission interviews held at the outpatient mental health care service. We observe four types of expanded answers which: (a) display competence in bureaucratic discourse; (b) move from the sphere of the public to the private; (c) deal with potential facethreats; and (d) pre-empt rejection. Although the former is actually an optimized way of collaboration with the biopolitical order, the latter three types can be seen as actions of resistance to classification, not only symbolically but also in material terms: resisting statistical criteria of exclusion allows clients to negotiate access to mental healthcare.